PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA MELALUI PENGGUNAAAN MODEL TEAM ASSISTED INDIVIDULIZATION (TAI) DI SMK NEGERI 1 LUMUT - Rahmatika Elindra; mega sari simanjorang (JURNAL MathEdu (Mathematic Education Journal), 2018)
This study aims to know whether there is students’ mathematic Problem Solving improvement through TAI learning model at the eleventh grade students of TKJ major of SMK Negeri 1 Lumut. The research was conducted by using Class Action Research (CAR) with 30 students as the sample. The research consists of two cycles. The first cycle showed (a) the score of using TAI learning model was 7.43 (enough category), (b) the average of students’ mathematic problem solving was 74.0, and (c) 70% students got minimal mastery criteria. The research was continued to the second cycle, the result showed (a) the score of using TAI learning model was 9.5 (very good category), (b) the average of students’ mathematic problem solving was 84.08, and (c) 93.3% students got minimal mastery criteria. It was concluded there is students’ mathematic problem solving improvement through TAI learning model at the eleventh grade students of TKJ major of SMK Negeri 1 Lumut.